Origin of Hydrocarbons Stability from a Computational Perspective: A Case Study of Ortho‐Xylene Isomers. Issue 6 (14th February 2020) - Mitoraj, Mariusz P.; Sagan, Filip; Szczepanik, Dariusz W.; de Lange, Jurgens H.; Ptaszek, Aleksandra L.; van Niekerk, Daniel M. E.; Cukrowski, Ignacy
Abstract: It is shown herein that intuitive and text‐book steric‐clash based interpretation of the higher energy "in‐in" xylene isomer (as arising solely from the repulsive CH⋅⋅⋅HC contact) with respect to the corresponding global‐minimum "out‐out " configuration (where the clashing C−H bonds are tilted out) is misleading. It is demonstrated that the two hydrogen atoms engaged in the CH⋅⋅⋅HC contact in " in‐in " are involved in attractive interaction so they cannot explain the lower stability of this isomer. We have proven, based on the arsenal of modern bonding descriptors (EDDB, HOMA, NICS, FALDI, ETS‐NOCV, DAFH, FAMSEC, IQA), that in order to understand the relative stability of " in‐in " versus " out‐out " xylenes isomers one must consider the changes in the electronic structure encompassing the entire molecules as arising from the cooperative action of hyperconjugation, aromaticity and unintuitive London dispersion plus charge delocalization based intra‐molecular CH⋅⋅⋅HC interactions. Abstract : Stable through cooperativity ? Superior stability of out‐xylene vs. in‐xylene is rooted, contrary to the text‐book intuitive 'steric‐based' wisdom, in the cooperative action of hyperconjugation, aromaticity and unintuitive London dispersion plus charge delocalization based intra‐molecular CH⋅⋅⋅HC interactions.